Some notes on Kansas coccidae - Shelton, Frank Sessions (My University, 1899)
Introduction: The Coccidae (scale-insects) constitute a very large, important and common but little known family of Homopterous insects. I say they are a large family, because they are found practically everywhere, though most abundantly in the tropics and less abundantly as one approaches the colder regions. We are all more or less familiar with them, from the specimens we have noticed on our cultivated plants, both in the house and in the garden. They are very important from an economic standpoint, because many of the farmers’ worst enemies belong to this class of insects. The notorious San Jose scale and the numerous other scales that infest the grasses and fruit trees (particularly the latter), will readily occur to the mind as examples. In spite of its being so common and of such importance, this family of insects has been rather slighted by entomologists; for the reason, probably, that they are small and uninteresting to the average eye. In 1895, between seven and eight hundred species had been described, whereas there are probably several time that number in existence.
Citation: Shelton, Frank Sessions. Some notes on Kansas coccidae. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Coccidae; Aspidiotus Ostreaeformis; Theses; Manuscripts (documents)